A Comparison Study of Radioactivity and Radiation Hazard Index between Legal and Illegal Cigarettes - Mohd Ariff, Muhammad Shafiq Najemee; Abdullah, Haslaile; A. Jalil, Siti Zura (International Journal of Integrated Engineering, 2018)
Radioactive nuclide which emits radiation and damages biological tissue is found in the cigarette. Illegal cigarettes are reported to contain higher toxic levels of the nuclide as compared to the legal cigarettes. Therefore, this study aims to compare the radioactive elements, concentration, radiation dose and Radiation Hazard Index (RHI) of the legal and illegal cigarettes. The natural radionuclides of Uranium-238 (238U), Thorium-232 (232Th) and Potassium-40 (40K) of six legal cigarette brands and six illegal cigarette brands were measured using a High Purity Germanium (HPGe) detector-based gamma spectroscopy system. The radioactive elements that were detected by gamma spectrometer were Lead-214 (214P) and Bismuth-214 (214Bi) from 238U decay series, Bismuth-212 (212Bi) and Actinium-228 (228Ac) from 232Th decay series and 40K. The activity and concentration of 238U for legal cigarettes were significantly higher than illegal cigarettes (p